Needs Analysis for Maritime ESP Courses of Iran’s Ports and Maritime Organization (PMO) - Mohammad Akbar Raeisi; Mansoor Ganji; Ali Beikian; Nahid Yarahmadzehi (Journal of English Language Teaching and Learning, 2022)
Limiting the scope of Maritime English (ME) courses to nautical subject matters, due to the conventional views who define ME as the global language used at sea, may not be based on a real needs analysis of English for Specific Purposes (ESP) courses in ports and maritime related organizations. Utilizing a mixed-methods approach, this study aimed to challenge this traditional perception through conducting an ESP needs analysis in Ports and Maritime Organization (PMO) of Iran. All the 17 departments’ managers and/or their delegates were interviewed, then a researcher-made questionnaire which was developed according to the interviews was distributed among the experts (70 respondents). The deductive content analysis was used for analyzing the qualitative part, and the quantitative data were analyzed through descriptive statistics. It was revealed that the overall needs of PMO in terms of ESP does not concord with conventional nautical-based Maritime English courses, and it in fact encompasses a much wider variety of content areas such as “port economic, marketing and investment, legal, tariffs, agreements and contracts, education, research, strategic port administration, logistics” etc.